Small Pox Marks Face - R. N. Sharma; S. N. Tandon (Indian Journal of Plastic Surgery, 1969)
An analysis of 57 cases collected between January 1959 to december 1968 at the Unit of Plastic Surgery, King George's Medical College, Lucknow, India is presented. The description of the various parts affected, technique and post-operative Management is outlined. A brief discussion and follow up has been discribed.